Creating comedy in satiric short stories by means of language tools - Aitbaeva, B.; Abduov, M.; Tuleubaeva, K.; Zhunusova, M.; Ametova, A. (Slovenska Vzdelavacia Obstaravacia, 2018)
This article describes semantic features of humorous literature. Thus, we have analyzed works written by Kazakh satirists. It was established that expressive-evaluative connotation involves information about the object evaluation. Evaluation is made in terms of positive and negative emotions. One can note that irony and humor created by Kazakh satirists are expressed by words with the opposite meaning and polysemantic word-play. The authors can use direct and associative meaning of formal and informal pronouns. In the analyzed linguistic passages represented by lexical and contextual antonyms, phonetic rhymes, amplification synonyms and rhetorical questions, convergence clearly shows an evaluation contrast between a character and the author.
Keywords: satire; features of artistic expression; stylistic contrast; phraseological combinations